FTIR-spectroscopic studies of the tantalum (V) species formed in 1-butyl-l-methyl-pyrrolidinium chloride—TaCl₅ ionic liquid with the additives of alkali halides - Babushkina, O.B.; Nauer, G.E. (Украинский химический журнал, 2005)
Ionic liquid 1-butyl-l-methyl-l-pyrrolidinium chloride—TaCl₅ (molar ratio 65:35) was synthesized with the aim of electrochemical deposition of tantalum coatings at ambient temperature. To elucidate the mechanism of the deDOsition process, FTIR spectroscopic studies were performed. A detailed analysis indicates the formation of TaCl₆⁻ complexes and some oxochloride complexes of tantalum (V) with bridge oxygen bonds Ta-O-Ta. Addition of alkali chlorides has no effect on the vibrational features of tantalum (V), whereas LiF leads to the formation of mixed complexes TaCl₆₋nFn⁻ with simultaneously decreasing amount of the tantalum (V) species with Ta-O-Ta bridge bonds.